APLIKASI METODE PENGENDAPAN PADA ANALISIS FITOPLANKTON DAN TINGKAT KESUBURAN WADUK SAGULING - Soetrisno, Yudhi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
At this moment, Saguling reservoir in Citarum river is not only polluted by waste water from municipal, industry, agriculture and become eutrophicated. This research was carried out in attempt to know how bad is the eutrophication and effecting phytoplankton in Saguling river. This research reveal based on the measured physical, chemistry and biological parameters, Saguling reservoir could be classified into eutrophic with low transparency (<70 cm), high concentration of nitrogen (>1,100 mgN•l-1), phosphor (>0,216 mgP•l-I) and dominated by Mycrocytis and Ascilatoria. This result also approved the previous analysis that overflow of sampling plankton- net always resulting “underestimation” value. Therefore using row metter without filtering and settling methode in phytoplankton is suggested.